State and private universities in the global education - (:unkn) unknown (Jaypee Brothers Medical Publishers (P) Ltd, 2013)
The impact of globalization opened countries in a competitive international economic market to be able to meet the challenges of global economy. According to these demands, the need of supplying human capital resulted in a change in the role of the universities. This paper discussed that global comparativeness has had divergent effects on the conceptualization and practices of higher education.
Keywords: Globalization; Labor productivity; State and private universities